Malnutrition and associated risk factors in orphanages in Punjab, Pakistan: an analytical study - Naveed Ali; Muhammad Farhan Farid; Alfur Rehman; Ahmad Mujtaba Khaliq; Ahmad Hussen Tareq (BMJ Nutrition, Prevention & Health)
Background Children living in orphanages face an increased susceptibility to malnutrition due to inadequate nutrition and psychological factors, in comparison to children who stay with their parents. A considerable proportion of institutionalised children remain unreported, and there is a dearth of information regarding the nutritional status of these children in Pakistan. This study set out to evaluate the status of malnutrition in the orphanages of Social Welfare Department Punjab.Methodology A multicentre analytical cross-sectional study was conducted from 12 December 2021 to 30 June 2022, with 255 study participants (aged 6–18 years) in seven orphanages (4 girls, 3 boys) out of 12 orphanages of government of Punjab. Anthropometric measurements were taken using standardised measuring instruments, and data were collected using structured questionnaire. Subjects were classed as malnourished based on body mass index for age and height for age reference growth charts of WHO 2007. Binary logistic regression was used to identify potential risk factors of malnutrition in orphanages.Results The study identified 36.1% malnourished children, of whom, 65.2% were orphans and 34% destitute children. The study reported 9.4% moderately underweight, 2.4% severely underweight, 4.3% overweight and 1.2% obese children and adolescents. The study established 17.6% moderately stunted, and 7.1% severely stunted children. Age at admission to orphanages (9–13 years) and lack of milk and meat consumption were identified as significant predictors of malnutrition in institutionalised children of Punjab.Conclusion Central Punjab had the highest malnutrition rate compared to North and South Punjab. Micronutrient deficiencies were more pronounced in South Punjab orphanages. Effective prevention of malnutrition requires early assessment of malnutritional risk in Pakistani orphanages.